Pharmacological effects of Radix Angelica Sinensis (Danggui) on cerebral infarction - Hsieh Ching-Liang; Wu Yi-Chian (BMC, 2011)
Abstract Radix Angelica Sinensis, the dried root of Angelica sinensis (Danggui), is a herb used in Chinese medicine to enrich blood, promote blood circulation and modulate the immune system. It is also used to treat chronic constipation of the elderly and debilitated as well as menstrual disorders. Research has demonstrated that Danggui and its active ingredients, as anti-arthrosclerotic, anti-hypertensive, antioxidant anti-inflammatory agents which would limit platelet aggregation, are effective in reducing the size of cerebral infarction and improving neurological deficit scores.